Development of an ethnomathematics-based digital flipbook module for least common multiple and greatest common divisor in the fourth grade of elementary school - Meita Fitrianawati; Tika Setiyawati (Universitas negeri Yogyakarta, 2021)
Indonesian school-age children generally have lower mathematics competence compared to those of other countries. One of the ways to solve this problem is through the introduction of the ethnomathematics approach associated with everyday life and culture. This study aims to develop and determine the quality and feasibility of the digital flipbook module with an ethnomathematics approach for the greatest common divisor and least common multiple materials for the fourth grade of elementary school. The data were collected through a questionnaire with quantitative and qualitative analysis. This study indicates that the current research and development has achieved the expected quality of the digital flipbook module, which has been validated by media, language, material, and learning experts. The score resulting from media validation was 84.4, the material expert was 84, linguists was 76, and learning expert was 88, and thus the average assessment of this module was 83.2, which is classified as a very good category. In terms of priorities, with limited trials, the assessment score of the teacher’s response was in the good category with 92, and the average score of student assessment was 94 or in a good category. The average assessment from expert validators, teachers, and students was 86.46, which was classified in a very good category. Thus, the digital flipbook module with an ethnomathematics approach for least common multiple (KPK) and greatest common divisor (FPB) materials developed by researchers is suitable for use in learning.